2015
DOI: 10.1002/hep.28266
|View full text |Cite
|
Sign up to set email alerts
|

Association between nucleos(t)ide analog and tumor recurrence in hepatitis B virus–related hepatocellular carcinoma after radiofrequency ablation

Abstract: Radiofrequency ablation (RFA) is the best choice for curative treatment of hepatocellular carcinoma (HCC) cases not suitable for surgical intervention, but efforts should be made to reduce the risk of tumor recurrence. We aimed to investigate the association between nucleos(t)ide analog (NA) therapy for hepatitis B virus (HBV) and the risk of HCC recurrence post-RFA. Using the Taiwan National Health Insurance Research Database between July 1, 2004 and December 31, 2012, we screened 48,807 patients with newly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 44 publications
5
76
0
Order By: Relevance
“…Nevertheless, the association is quite remarkable. Given the newly available and effective therapies for hepatitis B and C (and possibly also anti-inflammatory agent, such as aspirin, NSAIDS, Cox inhibitors, in patients without bleeding disorder), it may be that their use in suppressing hepatic inflammation and/or improving liver function in HCC patients with inflamed livers, offer the possibility of decreasing HCC aggressiveness through improvement of the underlying liver function [28][29][30][31][32]. What might be the mechanisms by which liver function parameters could influence HCC aggressiveness Two possible general explanations might be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the association is quite remarkable. Given the newly available and effective therapies for hepatitis B and C (and possibly also anti-inflammatory agent, such as aspirin, NSAIDS, Cox inhibitors, in patients without bleeding disorder), it may be that their use in suppressing hepatic inflammation and/or improving liver function in HCC patients with inflamed livers, offer the possibility of decreasing HCC aggressiveness through improvement of the underlying liver function [28][29][30][31][32]. What might be the mechanisms by which liver function parameters could influence HCC aggressiveness Two possible general explanations might be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrate that oral antiviral treatment using nucleos(t)ide (nucleoside/nucleotide) analog results in favorable outcomes in terms of tumor recurrence and overall survival of HBV-related HCC after surgical resection [1214]. However, a few studies have been carried out to explore on the effect of antiviral treatment on the prognosis of HBV-related HCC after curative RF ablation [15, 16]. Our group reported that the absence of antiviral therapy during follow up was associated with poor survival in HCC patients who received RF ablation as first-line therapy [15].…”
Section: Introductionmentioning
confidence: 99%
“…Our group reported that the absence of antiviral therapy during follow up was associated with poor survival in HCC patients who received RF ablation as first-line therapy [15]. Recently, Taiwanese investigators reported that nucleos(t)ide analog treatment is associated with a decreased risk of HCC recurrence using nationwide health insurance database [16]. However, previous studies did not provide detailed HBV-related data such as pretreatment HBV DNA levels or HBeAg status that are known as important factors affecting prognosis in HBV-related HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a cohort study of patients receiving curative liver resection for HCC in Taiwan demonstrated a significant risk reduction of tumor recurrence in patients receiving NAs versus untreated patients (45.6% vs. 54.6%, P < 0.001) [73]. This benefit was also seen following RFA (2-year recurrence rate: 41.8% vs. 54.3%; P < 0.05) [74].…”
Section: Nas Against Hcc Recurrence After Surgical Resection or Localmentioning
confidence: 54%